The mediating effects of resilience and coping strategies on perceived threat of Covid-19 and subjective well-being among Malaysian emerging adults - Hang, Siew Yi; Lin, Low Yi; Leong, Wong Chin; Ting, T'ng Soo; Ho, Khee Hoong (Universitas Negeri Padang, 2021)
The outbreak of COVID-19 has been affecting the Malaysian psychological well-being, particularly among emerging adults. They have been found to have higher vulnerability during the transitional life change. Therefore, the present study aims to examine the mediating effects of resilience and coping strategies (i.e., task-oriented coping, emotion-oriented coping, avoidance-oriented coping) on perceived threat of COVID-19 and subjective well-being (SWB) among Malaysian emerging adults. A cross-sectional online survey study was conducted for recruiting 162 participants. They were emerging adults aged between 18 to 25 years old (M = 22.51). The finding revealed that only task-oriented coping mediates the association between perceived threat of COVID-19 and SWB. However, the other hypotheses were not supported. This significant finding has widened the literature perspective of COVID-19 in the local context. Task-oriented coping is crucial to be cultivated among emerging adults for reducing the impact of the stressful situation, contributing to better psychological health.